Macromol. Chem. Phys. 18/2014. Issue 18 (September 2014) - Poonpong, Supawadee; Dwivedi, Sumant; Taniike, Toshiaki; Terano, Minoru; Sun, Wen‐Hua
<x xml:space="preserve">Abstract</x> Front Cover: This special issue is dedicated to Prof. Dr. Minoru Terano on the occasion of his 60th birthday, who has made substantial contributions to "Continuing Innovation in Polyolefin Catalysis and Materials". The work featured in the cover image delivers structure–performance relationships for alkoxysilane external donors in Ziegler–Natta propylene polymerization. A combination of stop‐flow polymerization and the coadsorption model successfully exploits the one‐to‐one correspondence between the experimental results and calculated performances for different donors. Further details can be found in the article by S. Poonpong, S. Dwivedi, T. Taniike, and M. Terano* on page 1721. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>